The Russian Revolution in Asia
1 online resource (xvii, 250 pages)
Keywords: "The Russian Revolution in Asia: From Baku to Batavia presents a unique and timely global history intervention into the historiography of the Russian Revolution of 1917, marking the centenary of one of the most significant modern revolutions. It explores the legacies of the Revolution across the Asian continent and maritime Southeast Asia, with a broad geographic sweep including Iran, the Caucasus, Central Asia, China, the Philippines, Vietnam, Indonesia, and India. It analyses how revolutionary communism intersected with a variety of Asian contexts, from the anti-colonial movement and ethnic tensions, to indigenous cultural frameworks and power structures. In so doing, this volume privileges Asian actors and perspectives, examining how Asian communities reinterpreted the Revolution to serve unexpected ends, including national liberation, regional autonomy, conflict with Russian imperial hegemony, Islamic practice and cultural nostalgia. Methodologically, this volume breaks new ground by incorporating research from a wide range of sources across multiple languages, many analysed for the first time in English-language scholarship. This book will be of use to historians of the Russian Revolution, especially those interested in understanding transnational and transregional perspectives of its impact in Central Asia and Southeast Asia, as well as historians of Asia more broadly. It will also appeal to those interested in the history of Islam"--